U-shaped relationship of perceived overqualification and job crafting: Moderation effect of psychology capital and work autonomy - Wahjudi, Ignacio Eric; Radikun, Tulus Budi Sulistyo (Jurnal Psikologi, 2024)
Background: The increase in the number of layoffs and periods of recession gave rise to an interesting phenomenon, namely overqualification of employees. Most research on overqualification and perceived overqualification (POQ) so far was conducted to look for negative impacts and was carried out in developed countries.Purpose: This study aims to explore the non-linear relationship and positive influence of POQ on job crafting, as well as the role of psychological capital and work autonomy in strengthening this relationship. Method: Data was collected from 217 employees with tenure ranging from 1 to 5 years, occupying positions at or below the supervisory level.Findings: The result of the main hypothesis showed that POQ has a U-shaped relationship with job crafting, which indicates that there is an optimal POQ level that can increase an employee’s job crafting. The research results also showed that high psychological capital in employees is able to moderate the relationship between POQ and job crafting, thus strengthening the relationship between the two. Work autonomy was found could not moderate the relationship between the two.Implication: It is expected that the results of this research can help companies overcome the negative impact of POQ and instead benefit from the positive impact.